(untitled) (Raparin Journal of Humanities (RJH), 2023)
Tourists will have a significant impact on these purchases and sales as a result of these well-designed and eye-catching advertising that appear and care about marketing. The general public services should provide the relevant details regarding the tourist destination as well as the amenities and services provided to them. Tourists will gain from participating in this tourism program; completing this task will not be unpleasant because it is a service. Tourism, unlike other things, is not always available, the items supplied to visitors cost more than that amount of money. The price of the services and the tourism sergeant will undoubtedly satisfy the visitors. Here, the visitor must return many than once in order for us to have a nice guest and also become a market catalyst for unpaid warm marketing. Previously, spreading the word about a place was done by "word of mouth," which meant telling friends to visit, but now we are all on the same scope. With the strength and effectiveness of the marketing campaign for visitors, we shouldn’t lose sight of the importance of an honest letter or marketing campaign that accurately describes the amenities and services offered by an institution or service provider.